Effects of Plyometric Jump Training on Physical Fitness in Amateur and Professional Volleyball: A Meta-Analysis - Ramirez-Campillo, Rodrigo; García-de-Alcaraz, Antonio; Chaabene, Helmi; Moran, Jason; Negra, Yassine; Granacher, Urs (Frontiers in Physiology, 2021)
We aimed to examine the effects of plyometric jump training (PJT) on measures of physical fitness in amateur and professional volleyball players. A systematic electronic literature search was carried out in the databases PubMed, MEDLINE, Web of Science, and SCOPUS. Controlled studies including pre-to-post intervention tests of physical fitness and involving healthy volleyball players regardless of age and sex were considered. A random-effects model was used to calculate effect sizes (ES) between intervention and control groups. Moderator analyses considered programme duration, training frequency, total number of training sessions and jumps, participants’ sex, age, and expertise level. The Physiotherapy Evidence Database scale was used to assess the methodological quality of the included studies. Eighteen moderate-to-high quality (median of 5 PEDro points) studies were eligible, comprising a total of 746 athletes. None of the included studies reported injuries related to the PJT intervention. The main findings showed small-to-moderate effects (p<0.05) of PJT on linear sprint speed (ES=0.70), squat jump (ES=0.56), countermovement jump (CMJ) (ES=0.80), CMJ with arm swing (ES=0.63), drop jump (ES=0.81), and spike jump height (ES=0.84). Sub-analyses of moderator factors included 48 data sets. Only age had a significant effect on CMJ performance. Participants aged ≥16 years achieved greater improvements in CMJ performance compared to <16 years old (ES = 1.28 and 0.38, respectively; p=0.022). No significant differences (p=0.422) were identified between amateur (ES=0.62) and professional volleyball players (ES=1.01). In conclusion, PJT seems safe and is effective in improving measures of physical fitness in amateur and professional volleyball players, considering studies performed in both male and female.